A novel in-situ test method for permeability in saturated sandy porous media. (October 2022) - Cao, Zeng; Liang, Xu; Deng, Yu; Chen, Bairu
Abstract: Permeability is a vital parameter for the design and construction of structures involving ocean engineering. Based on the steady-state heat transfer theory and Darcy's law, a novel in-situ test method for permeability in saturated sandy porous media is introduced in this work. This approach aims to obtain permeability through the inversion of the measured temperatures. Temperatures measuring device with a constant heater was installed in an insulating experimental tank filled with sandy sediments of different permeability. Further, a numerical model based on the Finite Element method was simulated to validate the feasibility of the proposed method and accuracy of the experimental data. Besides, the results obtained by the constant head test were compared with those calculated by the novel in-situ test method, considering different surface temperatures of the heater and different sediments' permeability. It shows that the permeability obtained by in-situ method are reliable and accurate (the accuracy is within one order of magnitude) in both numerical simulations and experimental tests. The effects of different surface temperatures of the heater and permeability of porous media on permeability calculation results were also discussed. The surface temperature was found that has little influence on permeability. And the proposed method is applicable when the permeability is higher than 10 −12 m 2 . The findings can provide some reference to the in-situ measurement of submarine sediments' permeability.